RPTRA CONCEPT IN THE ARCHIPELAGO: BASED ON AN EQUALITY AND LEGAL PROTECTION APPROACH - Septiady, Yophie; Tehupelory, Aartje (International Journal of Research -GRANTHAALAYAH, 2021)
The focus of the discussion in this study is on the design and needs of RPTRA in communities with different environmental and cultural contexts. Including the understanding of the surrounding community who "get" the RPTRA regarding the procedures for its use and maintenance. An equally important part is the concept of "child-friendly", what kind of understanding and implementation is there, and its legal basis (particularly for the protection of children in public spaces – RPTRA). This research was conducted on Tidung Island, one of the islands in the South Thousand Islands District, Seribu Islands Regency, DKI Jakarta Province. Several things that need to be considered as a reference in the development of RPTRA in archipelagic areas based on an architectural approach: (1) Access and affordability, (2) Community involvement in RPTRA design, (3) RPTRA which also basically pays attention to children with special needs, (4) Maintaining Green Open Space compared to the existence of buildings, (5) Prioritizing activity facilities that are the choice of the surrounding community, (6) RPTRA design must pay attention to weather conditions in coastal areas, (7) Socialization to the surrounding community on the character of materials and their use, (8 ) RPTRA designer’s understanding of zoning and facility classification, (9) Setting zoning activities between toddlers and youth, (10) Utilizing existing facilities outside the RPTRA. Several things that need to be considered as a reference in the development of RPTRA in archipelagic areas based on a legal approach are: (1) The legal aspects of establishing an RPTRA based on the ideal area, (2) The conception of RPTRA as accommodating the idea of ​​a child-friendly city based on existing regulations, (3 ) Legal studies to harmonize RPTRA with the PKK Main Program based on Governor Regulation Number 40 of 2016 have not gone well, (4) Legally (based on Governor’s Decree Number 349 of 2015 concerning the Implementation Team for RPTRA Development and Maintenance) the role of RPTRA managers must also be emphasized its main tasks and functions.